2005
DOI: 10.1038/sj.npp.1300787
|View full text |Cite
|
Sign up to set email alerts
|

COMT Polymorphisms and Anxiety-Related Personality Traits

Abstract: High neuroticism and low extraversion are characteristic of anxiety-prone individuals. A functional variant in the catechol-Omethyltransferase (COMT) gene, the Val158Met ('val/met') polymorphism, has been associated in some prior studies with several phenotypes, including neuroticism. We tested the hypothesis that the val158met polymorphism would be associated with both high neuroticism and low extraversion, making it a plausible candidate locus for anxiety susceptibility. To determine whether val158met is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
128
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(153 citation statements)
references
References 71 publications
18
128
3
2
Order By: Relevance
“…Our findings are in line with a recent study on phobic Association of COMT with panic disorder C Rothe et al anxiety that has been reported to be associated with the valine allele of the functional COMT polymorphism in a sample of 1234 women (McGrath et al, 2004). A recent association study of COMT and anxiety-related personality traits described two significant haplotypes which we found in our case-control sample significant as well (Stein et al, 2005). A study by Bray et al (2003) showed that apart from the Val/Met polymorphism, COMT variants are of functional importance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in line with a recent study on phobic Association of COMT with panic disorder C Rothe et al anxiety that has been reported to be associated with the valine allele of the functional COMT polymorphism in a sample of 1234 women (McGrath et al, 2004). A recent association study of COMT and anxiety-related personality traits described two significant haplotypes which we found in our case-control sample significant as well (Stein et al, 2005). A study by Bray et al (2003) showed that apart from the Val/Met polymorphism, COMT variants are of functional importance.…”
Section: Discussionsupporting
confidence: 93%
“…An association has been found also in schizophrenia (Goldberg et al, 2003;Shifman et al, 2002), major depression (Massat et al, 2005), rapid cycling in bipolar illness (Kirov et al, 1998) and anxiety-related personality traits (Stein et al, 2005). This might indicate that the involvement of COMT variants would be a 'general deficit' leading to several syndromes rather than to a 'specific deficit' associated to PD or any other particular syndrome.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Of note, several authors found that genetic variants of the COMT gene play a role in personality dimensions in female subjects but not in male subjects (Kim et al, 2006;Stein et al, 2005;Qian et al, 2003;Eley et al, 2003). Interestingly a sexually dimorphic effect of COMT Val158Met alleles was also found in ADHD patients, wherein the Val allele may contribute to ADHD risk in female subjects (Qian et al, 2003).…”
Section: Discussionmentioning
confidence: 99%